ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI VOLUME EKSPOR UDANG KE JEPANG PADA TAHUN 1993-2022 - Yehezkiel Anggi Hasudungan Naibaho; Ni Luh Karmini (E-Jurnal Ekonomi Pembangunan, 2024)
International trade has long been carried out by exporting or importing from two or more countries. Indonesia is a country that is rich in nature in all sectors, one of which is the fisheries sector. Indonesia is a large country with a wider water area, so it is said to be a maritime country. Indonesian shrimp are usually exported to several destination countries, one of which is Japan. Shrimp exports to Japan have fluctuated with a negative trend. Therefore, in this study variables are used that influence the volume of shrimp exports to Japan, namely, GDP per capita, domestic shrimp prices, competitors' shrimp prices, and the exchange rate against. This research uses secondary data with an annual period from 1993 to 2022. The results of this research show that“GDP per capita, domestic shrimp prices, competitors' shrimp prices, and exchange rates simultaneously influence the volume of shrimp exports to Japan. Partially, GDP per capita has a negative and significant effect on shrimp exports, domestic shrimp prices have a negative and significant effect on shrimp exports, competitors' shrimp prices have a positive and significant effect on shrimp exports, and the exchange rate has a positive and insignificant effect on shrimp exports.”